Vegetarian Diet in Children: Benefits, Drawbacks and Risks - Orzeł, Adrianna; Sieniawska, Julia; Sieniawska, Daria; Proszowska, Patrycja; Kotowicz, Zuzanna; Pich-Czekierda, Aleksandra; Madoń, Magda (Journal of Education, Health and Sport, 2024)
Introduction Vegetarianism is an eating pattern centred on plant-based food. It encompasses many diets that differ in terms of whether they contain goods originating from animals, like milk and eggs. Nowadays, vegetarianism is increasing in popularity in developed nations, particularly in Europe. Individuals choose vegetarian diets for reasons related to health, ethics, or ecology. The rising popularity of vegetarian diets is not limited to adults but is also increasing among children. Aim of the study Vegetarian diets are generally considered to be beneficial for health. However, there are concerns over the ability to meet the dietary requirements necessary during infancy, youth, and adolescence on a vegetarian diet. Therefore, the primary aim of this systematic review is to answer questions about the efficacy of a plant-based diet in meeting the nutritional requirements of children and how to avoid the risk of nutritional deficiencies among vegetarian children. Material and methods Article provides an overview of the current literature about the vegetarian diet in children. The information has been collected from a comprehensive search of electronic databases, scientific journals, and statement papers published by nutrition and paediatric organisations. Results Following a vegetarian diet can be a beneficial decision for all children, assuming that it is properly organised and well balanced. The majority of paediatric and nutrition organisations do not recommend more strict diets for children, such as a vegan diet, which fully excludes not only meat but all animal products.